2016
DOI: 10.1371/journal.pone.0157361
|View full text |Cite
|
Sign up to set email alerts
|

Serum Alkaline Phosphatase Levels Predict Infection-Related Mortality and Hospitalization in Peritoneal Dialysis Patients

Abstract: BackgroundSerum alkaline phosphatase (ALP) levels have been reported to be associated with all-cause and cardiovascular mortality in peritoneal dialysis (PD) patients. However, it is unclear whether serum ALP levels predict infection-related clinical outcomes in PD patients. The aim of this study was to determine the relationships between serum ALP levels, infection-related mortality and hospitalization in PD patients.MethodsPD patients from the Clinical Research Center registry for end-stage renal disease, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…A renoprotective action of ALP through reduced inflammation and oxidative stress was reported, [3,6,29] whereas a strong association was found between higher ALP level and poor prognosis in patients with kidney disease. [9,10,20,26] Our analysis revealing a biphasic relationship between the ALP tertiles and dialysis requirement, despite the lack of statistical significance, may be explained in this context.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A renoprotective action of ALP through reduced inflammation and oxidative stress was reported, [3,6,29] whereas a strong association was found between higher ALP level and poor prognosis in patients with kidney disease. [9,10,20,26] Our analysis revealing a biphasic relationship between the ALP tertiles and dialysis requirement, despite the lack of statistical significance, may be explained in this context.…”
Section: Discussionmentioning
confidence: 78%
“…[5] Accordingly, increased serum ALP level is considered a cellular response to inflammatory stimuli such as bacterial invasion. [3] In this regard, there are several reports on the association of higher serum ALP level and infection-related death both in patients undergoing dialysis [26] and in those with normal renal function. [27] Our finding of a close relationship between ALP level and the composite of endpoints could also be at least partly attributable to infection and sepsis-related mortality, although there was no significant association of ALP level and infection per se.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study, the Dialysis Outcomes and Practice Patterns Study (DOPPS), found that elevated serum ALP level was associated with higher risk of infection-related death in HD patients, independent of calcium, phosphorus, and iPTH levels [25]. Two recent multicenter prospective studies in Korea also showed that elevated serum ALP level and low serum phosphorus level were independently associated with higher risk of infection-related mortality in dialysis patients [32,33]. To the best of our knowledge, the present study is the first multicenter prospective study showing significant associations between serum iPTH level and mortality risk of infection, rather than cardiovascular disease, in incident dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD, mineral and bone disease (MBD) can cause abnormal serum concentration of calcium, phosphorus, parathyroid hormone (PTH), fibroblast growth factor 23 (FGF23), and alkaline phosphatase (ALP), resulting in bone-related abnormalities and vascular calcification. This complication is associated with increased mortality by CVD or infectious disease 614 .…”
Section: Introductionmentioning
confidence: 99%